Guidelines for the development of an induction programme for the Education Management Development Centre, Metropole South District - Mlindazwe, Thozama (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPA (Public Management and Planning))--University of Stellenbosch, 2010.